Modeling the Physics of Bubble Nucleation in Histotripsy - de Andrade, Matheus O.; Haqshenas, Seyyed Reza; Pahk, Ki Joo; Saffari, Nader (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2021)
This work aims to establish a theoretical framework for the modeling of bubble nucleation in histotripsy. A phenomenological version of the classical nucleation theory was parametrized with histotripsy experimental data, fitting a temperature-dependent activity factor that harmonizes theoretical predictions and experimental data for bubble nucleation at both high and low temperatures. Simulations of histotripsy pressure and temperature fields are then used in order to understand spatial and temporal properties of bubble nucleation at varying sonication conditions. This modeling framework offers a thermodynamic understanding on the role of the ultrasound frequency, waveforms, peak focal pressures, and duty cycle on patterns of ultrasound-induced bubble nucleation. It was found that at temperatures lower than 50 degrees C, nucleation rates are more appreciable at very large negative pressures such as -30 MPa. For focal peak-negative pressures of -15 MPa, characteristic of boiling histotripsy, nucleation rates grow by 20 orders of magnitude in the temperature interval 60 degrees C-100 degrees C.
Keywords: HOMOGENEOUS NUCLEATION; ULTRASOUND; CAVITATION; TISSUE; MECHANISMS; NUCLEI